In depressed older persons higher blood pressure is associated with symptoms of apathy. The NESDO study. (5th March 2015) - Moonen, J. E. F.; de Craen, A. J. M.; Comijs, H. C.; Naarding, P.; de Ruijter, W.; van der Mast, R. C.
ABSTRACT: Background: In older persons, a relationship between both higher and lower blood pressure and depression has inconsistently been reported. Blood pressure may be differentially associated with distinct symptom domains of depression. We examined the cross-sectional relation of current systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP) with different depressive symptom domains among depressed older persons. Methods: In the Netherlands Study of Depression in Older Persons (NESDO), 270 participants aged 60 years and above were diagnosed with depression in the past month. Using the three corresponding subscales of the Inventory of Depressive Symptoms-Self Report (IDS-SR), motivational, mood and somatic symptom domains were assessed. Additionally, symptoms of apathy were determined with the Apathy Scale. Multiple linear regression was used to examine the cross-sectional relationship between current SBP, DBP and MAP with both IDS-SR subscale and Apathy Scale scores. Unstandardized betas were calculated per 10 mmHg increase in blood pressure measures. Results: Mean age of participants was 70.4 years (standard deviation 7.3). Higher SBP (Beta 0.33, t (254) = 2.01, p = 0.045), higher DBP (Beta 0.68, t (254) = 2.15, p = 0.03) and higher MAP (Beta 0.63, t (254) = 2.33, p = 0.02) were associated with higher Apathy Scale scores in the fully adjusted model. Furthermore, a higher SBP was associated with higher IDS-SR mood subscale scores (Beta 0.25, t (254) = 2.13, p = 0.03). Conclusions: Depressed older people with higher blood pressure measures had particularly more symptoms of apathy. To disentangle the relationship of blood pressure with late-life depression, it is important to pay attention to the role of apathy symptoms.